Insights into a Mineral Resource Chlorite Mica Carbonate Schist by Terahertz Spectroscopy Technology - Meihui Yang; Siqi Zhang; Haochong Huang; Yuanyuan Ma; Sibo Hao; Zili Zhang; Zhiyuan Zheng (Energies, 2022)
Nowadays, the mineral resources formed by geological processes have been effectively utilized with the boom exploration of novel technologies. Traditional analytical methods, such as X-ray Fluorescence, X-ray diffraction, and Scanning electron microscopy, remain the commonly used approaches for resource detection. However, recent accelerations in terahertz component progress have promoted researchers to discover more potential technologies in mineral resource exploration. In this article, the various porosities and calcination products of Chlorite mica carbonate schist, a mineral resource and potent medicine, are detected using the terahertz time–domain spectroscopy. The terahertz constant measurement of Chlorite mica carbonate schist tablets including the amplitude and phase values was carried out. After Fourier transforms, notable differences of absorption coefficients and refractive index are observed from these experimental samples, which have compelling indications to quantitatively analyze the pore conditions and pyrolytic properties of mineral resources. This active research has vital implications for the rock reservoir properties analysis and mineral energy utilization. It is also identified that terahertz time–domain spectroscopy can be considered as a promising method for the qualitative, reliable, and efficient detection of mineral resources.